Small And Medium-Sized Business Development In Regions: Establishment Of Priority Directions By The Example Of Sverdlovsk Region - Tolmachyov, Dmitry Yevgenyevich; Ulyanova, Yelizaveta Andreyevna; Pliner, Lyudmila Markovna (Economy of Regions, 2015)
The paper presents the research of current small and medium-sized business development in Sverdlovsk region. It includes analysis of enterprise development statistics, Russian and international experience, sociological survey of entrepreneurs’ satisfaction of doing business conditions in Sverdlovsk region. The aim of the research was to develop proposals for business support system development in the long run for inclusion in the SME Development Strategy in Sverdlovsk region up to 2030. As a result, a set of strategic SME development directions was formulated. It includes measures aimed at business problems solving through the development of SME support tools and at addressing institutional problems of business support. The paper includes proposals for improvement of regional support system and implementation the priority SME development direction.